Welfare and inequality effects of debt consolidation processes: The case of Spain, 1996-2007 - Miguel Viegas; Ana Paula Ribeiro (SERIEs - Journal of the Spanish Economic Association, 2015)
The Spanish debt consolidation between 1996 and 2007 represents, by its size and duration, an impressive case among the European Union countries. This paper aims at characterizing the Spanish debt consolidation process in order to assess its effects on economic inequality and welfare. For that purpose we built a general equilibrium heterogeneous-agent model capable of exploring the relationship between fiscal policy variables and the endogenous cross-section distribution of income and wealth. The results show a quite impressive positive welfare gain despite significant transition costs. The simulations point to an increase of inequality during the initial transition period, reversing to more compressed distributions as the economy evolves to its final steady state equilibrium. Overall, the welfare gains are slightly biased towards wealthier individuals. Furthermore empirical data on the dynamics of some crucial variables during the consolidation period lend support to the model simulation results.
Keywords: E17; E60; H60; I30; 330; European Union; Fiscal consolidation dynamics; Heterogeneous agent model; Inequality; Spain; Welfare